2022 IEEE 63rd Annual Symposium on Foundations of Computer Science (FOCS) 2022
DOI: 10.1109/focs54457.2022.00022
|View full text |Cite
|
Sign up to set email alerts
|

Pure-Circuit: Strong Inapproximability for PPAD

Abstract: The current state-of-the-art methods for showing inapproximability in PPAD arise from the ε-Generalized-Circuit (ε-GCircuit) problem. Rubinstein (2018) showed that there exists a small unknown constant ε for which ε-GCircuit is PPAD-hard, and subsequent work has shown hardness results for other problems in PPAD by using ε-GCircuit as an intermediate problem.We introduce Pure-Circuit, a new intermediate problem for PPAD, which can be thought of as ε-GCircuit pushed to the limit as ε → 1, and we show that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Theorem 1 ( (Deligkas et al 2022a)). PURE-CIRCUIT is PPAD-complete, even when every node of the interaction graph has in-degree at most 2 and total degree at most 3.…”
Section: The Pure-circuit Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Theorem 1 ( (Deligkas et al 2022a)). PURE-CIRCUIT is PPAD-complete, even when every node of the interaction graph has in-degree at most 2 and total degree at most 3.…”
Section: The Pure-circuit Problemmentioning
confidence: 99%
“…This was recently improved by a result of Deligkas et al (Deligkas et al 2022a). They showed that it is PPADcomplete to find a 1/48-NE of a two-action polymatrix game, and it is PPAD-complete to find an ε-WSNE of a two-action polymatrix game for all ε < 1/3 (the latter result being tight).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations